Public perception towards sustainable mangrove forest programs in Malaysia - Wahid Marican, Nurshahirah; Mohd Nawi, Nolila; Kamarulzaman, Nitty Hirawaty; Samdin, Zaiton (Penerbit UMT, 2018)
The mangrove forest has been an important vegetative aspect in maintaining an ecosystem balance. Among its benefits is to cover the source of timber, charcoal, woods, herbs, and fish and shrimp culture where all of this can be valued as economic resources. Even with vast benefits it offers, the number of mangrove forests are constantly declining and if there are no actions being taken, the mangrove forests may face the possibility of extinction. Degradation of mangrove forests in Malaysia is mainly due to development and agriculture. A sustainable mangrove forest is not something that is newly introduced in Malaysia as the Matang forest is known for its sustainable forest management for over 100 years. Sustainable mangrove forest programs do not only involve the necessary authorities but also the public as their participation in replanting and managing the mangrove forest. Thus, this study aims to determine the public perception towards sustainable mangrove forest programs in Malaysia. Data were collected via face-to-face interviews with respondents from the states which have high percentage of mangrove forests such as Perak, Sabah, Selangor, Johor, and Pahang. Prior to actual data collection, a pilot study was conducted in Kuala Selangor with 100 respondents. Respondents were selected by using a simple random sampling technique from mangrove and non-mangrove areas with a total of 871 respondents. Data collected were analyzed using descriptive analysis and chi-square analysis. Descriptive analysis has found that the public perception towards the importance of mangrove forest is high with the overall mean score of 4.09. The chi-square analysis revealed that gender, age, education level, income, marital status, and family members have significant relationships with the public perception towards sustainable mangrove forest programs. The insight of this study can help the government and NGOs to organize campaigns and programs related to sustainable mangroves forest more effectively.